Effects of Rubus discolor flower extract on the fatty acid composition in hydrogen peroxide administered Wistar rats - Keser, Serhat; Çelik, Sait; Türkoğlu, Semra; Yılmaz, Ökkeş; Türkoğlu, İ?smail (My University, 2014)
The aim of this research is to examine possible protective effects of Rubus discolor (RD) flower extracts on the fatty acid contents of some tissues, which hydrogen peroxide (HP) administered Wistar rats. In present study, Wistar rats were randomly divided into four groups: 1. Control (C), 2. Hydrogen Peroxide (HP), 3. Rubus discolor (RD), 4. Rubus discolor + Hydrogen Peroxide (RD+HP). In tissues, fatty acid content analyses were performed by gas chromatography. According to our results, while fatty acid levels were barely affected in the heart, muscle, brain and spleen tissues of HP group, but these levels were affected in the serum, liver, kidney and lung tissues of the same group when compared to the control group. The fatty acid contents were changed in all tissues of RD and RD+HP groups when compared to control group. Our results confirm that RD and HP treatment have affected the amount of important fatty acids, which substrates in fatty acids metabolism of Wistar rats. In also, this study is first report about the effects of R. discolor flower extract on the fatty acid composition.

Bu çalışmanın amacı hidrojen peroksit (HP) uygulanmış Wistar sıçanların bazı dokularının yağ asidi içeriği üzerinde Rubus discolor (RD) çiçek ekstresinin olası koruyucu etkilerini incelemektir. Sunulan çalışmada, Wistar sıçanlar rastgele 4 ayrı gruba ayrıldı: 1. Kontrol (C), 2. Hidrojen Peroksit (HP), 3. Rubus discolor (RD), 4. Rubus discolor + Hidrojen Peroksit (RD+HP). Dokulardaki yağ asidi içeriği gaz kromatografisi cihazıyla analiz edildi. Sonuçlarımıza göre, kontrol grubuyla karşılaştırıldığı zaman, HP grubunun kalp, kas, beyin ve dalak dokusunda yağ asidi seviyeleri hemen hemen hiç etkilenmezken, aynı grubun serum, karaciğer, böbrek ve akciğer dokularında yağ asitleri seviyeleri etkilenmiştir. RD ve RD+HP gruplarının bütün dokularında yağ asidi içeriği kontrol grubuna göre değişmiştir. Sonuçlarımız göstermiştir ki RD ve HP uygulaması, Wistar sıçanların yağ asidi metabolizmasında substrat olan bazı önemli yağ asitlerinin miktarını etkilemiştir. Ayrıca bu çalışma R. discolor çiçek ekstresinin yağ asidi içeriği üzerindeki etkileri hakkında ilk rapordur.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Rubus discolor; Hydrogen peroxide; Wistar rat; Fatty acid